Mali : Request for Second Tranche of Debt Service Relief Under the Catastrophe Containment and Relief Trust-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic and the August 2020 coup d'etat have disrupted more than half a decade of strong economic performance, during which growth averaged 5 percent.1 Growth is projected to decline from 5 percent to -2 percent in 2020 both on account of the pandemic (reflecting a slowdown in external demand, travel, and FDI, as well as the impact of uncertainty and reduced mobility on domestic demand) and of post-coup disruptions in trade, transport, economic and financial flows following the sanctions imposed by the Economic Community of West African States (ECOWAS). Inflation accelerated slightly in recent months but is expected to remain below 2 percent, while the current account deficit is projected to narrow due to higher gold prices (main export) and lower oil prices (main import). Risks around the outlook are exceptionally high in light of the uncertainty surrounding the political transition, the impact of the sanctions on trade and overall activity, and continued deterioration in the security situation. Weak social safety nets amid high informality, food insecurity and a fragile healthcare system exacerbate challenges.